Diversity of Piophilidae (Diptera) in northern Canada and description of a new Holarctic species of Parapiophila McAlpine - Rochefort, Sabrina; Wheeler, Terry A. (Zootaxa, 2015)
Piophilidae (Diptera) were inventoried at 12 sites in boreal and arctic Canada as part of the 1947–1962 Northern Insect Survey and 2010–2011 Northern Biodiversity Program. Seventeen species were identified, including a new Holarctic species: Parapiophila kugluktuk sp. n. which is widespread in North America and northern Sweden. Allopiophila calceata Duda is considered a junior synonym of Parapiophila atrifrons (Melander & Spuler) syn. n. based on morphological and molecular evidence. Parapiophila baechlii Merz, previously known from Switzerland, is newly recorded in the Nearctic region, as well as Sweden and northeastern Russia (Cherskiy). Parapiophila pectiniventris (Duda), previously known from the Palaearctic region and Greenland, is newly recorded from North America. Species richness was highest in mainland subarctic sites (16 species, 246 specimens). Five species (13 specimens) were collected in boreal sites, and five species (701 specimens) were collected on the high arctic island sites.